"The edTPA took away from my student teaching experience": The impact of the edTPA on student teaching experiences. (September 2019) - Shin, Minsun
This colloquium brings forward the "inside" voices of early childhood student teachers in order to critically examine the impact of the edTPA (Educative Teacher Performance Assessment) on student teaching experiences, especially the "educative" function that the edTPA claims.